하악과성장형과 상악열성장형 골격성 Ⅲ급 부정교합군간의 두개저 형태 비교 - 강동화(Dong-Hwa Kang); 권대근(Tae-Geon Kwon); 이상한(Sang-Han Lee); 김현수(Hyun-Soo Kim) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2007)
This study was intended to compare the cranial base morphology between the mandibular prognathism and maxillary retrognathism in skeletal class Ⅲ patients. The subject of the present study was composed of 88 patients divided into two groups; Group 1 (Skeletal Class III with mandibular prognathism. SNA within normal range, SNB over normal range, n=54) and Group 2(Skeletal Class III with maxillary retrognathism. SNA below normal range, SNB within normal range, n=34). Lateral cephalogram were taken immediate before surgery and 18 landmarks were used to analyze the characteristics of cranial base and maxillomandibular skeleton. The result revealed that cranial base angle is significantly smaller in Group 1 than Group 2, which implies the influence of the cranial base angulation on the mandibular position. However the posterior cranial base length did not influence the mandibular horizontal position and anterior cranial base length did not influence the maxillary horizontal position. As the anterior cranial base length was closely related with ramal height, it is recommendable to investigate the regulatory mechanism of chondrogenesis of cranial base and condyle cartilage in the future research. KCI Citation Count: 0